A new dynamic N2O reduction system based on Rh/ceria–zirconia: from mechanistic insight towards a practical application. Issue 2 (25th November 2020) - Wang, Yixiao; de Boer, Jorrit Postuma; Makkee, Michiel
Abstract : Simultaneous reduction of N2 O in the presence of co-existing oxidants, especially NO, from industrial plants, is a challenging task. Abstract : Simultaneous reduction of N2 O in the presence of co-existing oxidants, especially NO, from industrial plants, is a challenging task. This study explores the applications of a hydrocarbon reduced Rh/Zr stabilized La doped ceria (Rh/CLZ) catalyst in N2 O abatement from oxidant rich industrial exhaust streams e.g. NO, CO2, and O2 . The reaction mechanism was studied by the temporal analysis of products. The obtained results revealed that hydrocarbon pretreatment led to the creation of ceria oxygen vacancies and the formation of carbon deposits on the Rh/CLZ catalyst surface. These ceria oxygen vacancies are the active sites for the selective reduction of N2 O into N2, while the dissociated O atoms from N2 O fill the ceria oxygen vacancies. The oxidation of the deposited carbon via the lattice ceria oxygen generates new ceria oxygen vacancies, thereby extending the catalytic cycle. The reduction of N2 O over C3 H6 reduced Rh/CLZ is a process combining oxygen vacancy healing and deposited carbon oxidation. The results obtained from fixed-bed reactor experiments demonstrated that the hydrocarbon reduced Rh/CLZ catalyst provided a unique and extraordinary N2 O abatement performance in the presence of co-existing competing oxidants (reactivity order: N2 O ∼ NO > O2 > CO2 ∼ H2 O).